Broadband, White Light Emission from Doped and Undoped Insulators. (17th November 2017) - Tabanli, S.; Yilmaz, H. Cinkaya; Bilir, G.; Erdem, M.; Eryurek, G.; Bartolo, B. Di; Collins, J.
Abstract : We present data on broadband, white light emission from insulating hosts under intense excitation in the near infrared in host materials that are undoped, partially-doped with rare earth ions, and that contain stoichiometric concentrations of rare earth ions. Much of the emission is found to have a blackbody-like structure in the visible and near infrared region. The origin of the emission as from a blackbody is also supported by the temporal characteristics of the emission in response to turning on and off the laser, and also by the dependence of the air pressure in the chamber. However, some of the data presented cannot be explained by blackbody emission alone, so other processes are proposed to explain the observed spectra. The role of the rare earth ion dopants in enhancing the broadband emission is also considered.